2022
DOI: 10.3389/fonc.2022.900305
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-related parameter serve as prognostic biomarker in esophageal squamous cell carcinoma

Abstract: ObjectiveThe aim of this study was to explore the predictive role of inflammation-related parameters in prognosis of esophageal squamous cell carcinoma (ESCC).MethodsA total of 370 ESCC patients subjected to curative surgery were enrolled. All patients had complete medical records and did not receive preoperative adjuvant therapy. Preoperative systemic immune-inflammation index (SII) was calculated as platelet count × neutrophil count/lymphocyte count, prognostic nutrition index (PNI) as albumin concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As many studies have reported, these biomarkers are involved in the development, angiogenesis, and invasion of ESCC. [37][38][39] As a result, using data from the TCGA and HPA databases, we comprehensively investigated the expression of NRF2/HO-1, BIRC5, and TP53 in patients with esophageal carcinoma. We discovered that the expression levels of the aforementioned four transcription factors were substantially higher than those of the normal samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As many studies have reported, these biomarkers are involved in the development, angiogenesis, and invasion of ESCC. [37][38][39] As a result, using data from the TCGA and HPA databases, we comprehensively investigated the expression of NRF2/HO-1, BIRC5, and TP53 in patients with esophageal carcinoma. We discovered that the expression levels of the aforementioned four transcription factors were substantially higher than those of the normal samples.…”
Section: Discussionmentioning
confidence: 99%
“…As many studies have reported, these biomarkers are involved in the development, angiogenesis, and invasion of ESCC. 3739…”
Section: Discussionmentioning
confidence: 99%
“…The treatment outcomes and the occurrence of postoperative complications in oncology patients are often related to their nutritional status, which can be impaired by cancer-induced chronic inflammation [ 15 ]. In a large number of cancers, it has been shown that biomarkers of the inflammatory response can predict the prognosis and outcomes of these patients [ 16 , 17 , 18 , 19 ]. In recent years, the focus of numerous studies with oncology patients has been markers that can be calculated from blood count parameters such as the neutrophil-to-lymphocyte ratio (NLR) [ 20 , 21 ], the derived neutrophil-to-lymphocyte ratio (dNLR), the systemic immuno-inflammatory index (SII), and the systemic inflammatory response index (SIRI) [ 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%